Heritability for growth characteristics through the years in the Blanco Orejinegro breed - Fernández N., Juan Carlos (2021)
The aim of this study was to estimate the values of direct and maternal heritability and the variances due to the permanent environment from 1990 to 2012 in the Colombian Creole Blanco Orejinegro breed. In total, 10 698 data on growth variables were analyzed for birth weight (BW), adjusted weight at 240 days (PAJ240) and adjusted weight at 480 days (PAJ480). The derivative-free restricted maximum likelihood methodology (DFREML) was used, adjusting an animal model that included direct genetic effects, maternal and variations due to the permanent environment, assuming as fixed effects the year, time of birth, the sex of the calf and as covariate the mother's age at delivery. The heritability for BW were h²d = 0.31, h²m = 0.03 and σ²c = 0.07. the heritability values for PAJ240 were moderate and low (h²d = 0.18, h²m = 0.05, σ²c = 0.04) while for PAJ480 they were h²d = 0.17, h²m = 0.04, σ²c = 0.06, without presenting significant values and the proportion of the variances presented negative and decreasing values on the line. The genetic trends were increasing and decreasing, indicating that the environmental variance negatively affects the maternal component and the permanent environment for the weight at 240 and 480 days, respectively.